ANALISIS BUTIR SOAL ULANGAN AKHIR SEMESTER MATA PELAJARAN BAHASA INDONESIA KELAS XI - Agustiana, Mega; Mayrita, Hastari; Muchti, Andina (Jurnal Ilmiah Bina Edukasi, 2018)
The analysis uses SPSS Version 22 and Anates program version 4. Results study, (1)  quality of multiple choice questions is very difficult with 12 questions, difficult to number 25 items, the number is 6, and easy to 7. There are 3 questions, and 2 items are easy, (2) the quality of multiple choice questions is based on the distinguishing power, there are 32 items, the questions have enough differentiating power of 16 points, and items that have a negative differentiation are 2 questions; the description of the distinguishing power is quite 3 questions, and discriminating power is 2 questions, (3) quality of multiple choice questions is based on validity; valid 31 questions, 19 invalid questions. The description problem, classified as valid 5 questions, (4) quality of multiple choice questions based on reliability, has a high reliability coefficient of 0.898, while the problem of unreliable descriptions with a coefficient of 0.093